PENERAPAN NUMBERED HEAD TOGETHER (NHT) TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS X SMA NW SUKARARA TAHUN AJARAN 2017/ 2018 - Asri, Indra Himayatul (Cocos Bio, 2020)
Education has a central role in the development of a country's development and therefore education is an important concern every government even more so in Indonesia there are still some problems in the world of education, one of which is the low cognitive learning outcomes of students, especially in biology subjects that require an can overcome these problems. The purpose of this study was to determine the Effect of STAD (Reading Concept Mapping Student Teams Achievement Devision) Remap Learning Model with Lesson Study Patterns on Cognitive Learning Outcomes of Class XI Students of SMA Negeri 1 Sukamulia 2017/2018 Academic Year. This type of research is experimental research using Quasi Experimental Design. The population in this study students of class XI IPA semester I consisting of 2 classes with a total of 55 students. The sample in this study is class XI IPA 1 as the experimental class and class XI IPA 2 as the control class using simple random sampling technique. The instruments in this study were tests of cognitive learning outcomes in the form of essay tests totaling 8 items. Based on the results of data analysis obtained the average value of the experimental class posttest is 78.82 and the control class is 66.56. While the hypothesis test using statistical analysis with the t-test formula at the 5% confidence level is obtained by tcount of 6.97. after compared with t table 1.404, then tcount 6.97> t table 1.404, so that the conclusion in this study is that there is an effect of STAD (Reading Concept Mapping Student Teams Achievement Devision) Remap Learning Model with Lesson Study Patterns on Cognitive Learning Outcomes of Class XI Students of SMA 1 Sukamulia Year 2017/2018 teaching.